Analysis of the Interaction between Passengers and Buses at a Congested Bus Stop through Simulation to Reduce Congestion Rate - Nieto, Ronaldo Cuchilla (2025)
This article addresses the issue of user congestion at a high-demand public transportation stop in Lima, caused by prolonged waiting times and the perceived low quality of service. Micro simulation was conducted using VISSIM software to model ideal scenarios based on empirical data. The analysis considered key indicators such as service demand, congestion levels, and operational frequency of transportation lines. The study simulated the anticipated behavior of users who, upon having access to real-time bus arrival information, arrive at the stop just in time, thereby reducing waiting times. The results showed a 12.22% reduction in user congestion during peak hours and a more uniform redistribution of service demand during the same period. This optimization improved passenger flow and user experience without the need to alter the current bus frequencies, validating the economic and operational feasibility of the proposal. The research highlights the use of micro-simulation as an effective tool for designing sustainable solutions in urban environments, contributing to improved mobility and perceived reliability of public transportation.